ANALISIS KOMUNITAS ONLINE KITA MENGABDI SUMSEL - Saputri, Cindy (Jurnal Dinamika Sosial Budaya, 2022)
The Kita Mengabdi Sumsel Community is a community founded on September 24, 2020 online. This community has a vision and mission to develop remote areas in the South Sumatra region. Initially, the Kita Mengabdi Sumsel community was only founded by three administrators, until now this community has 23 members consisting of various professions and regions of origin. What makes this community unique and different from other communities is that the Kita Mengabdi Sumsel community only consists of administrators and does not have members in it. In addition, this community stands online so that in its implementation, as well as meetings, it also runs online so sometimes it causes some problems internally.